2019
DOI: 10.1371/journal.pone.0214375
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods analysis of factors affecting antenatal care content: A Syrian case study

Abstract: BackgroundMaternity care services provide critical interventions aimed at improving maternal and newborn health. In this study, we examined determinants of antenatal care (ANC) content in Syria, together with changes over time.MethodsWe analysed two national surveys conducted by the Central Bureau of Statistics in Damascus (PAPFAM 2001 and MICS 2006). Findings of this initial analysis led to a qualitative study on adequacy of antenatal care content in two Syrian governorates, Aleppo and Latakia in 2010, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
(37 reference statements)
0
10
2
1
Order By: Relevance
“…Latin America and the Caribbean was the region with higher average scores and less variability between countries. Although our results show that globally more than half of women scored between 7 and 9 points (55%), 7% received no care during pregnancy, which may be explained by contextual and individual factors 25,26 . A systematic review of factors affecting the utilization of ANC in LMICs showed that maternal education, household income, cultural belief and place of residence have an important influence on ANC coverage.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Latin America and the Caribbean was the region with higher average scores and less variability between countries. Although our results show that globally more than half of women scored between 7 and 9 points (55%), 7% received no care during pregnancy, which may be explained by contextual and individual factors 25,26 . A systematic review of factors affecting the utilization of ANC in LMICs showed that maternal education, household income, cultural belief and place of residence have an important influence on ANC coverage.…”
Section: Discussioncontrasting
confidence: 69%
“…Although our results show that globally more than half of women scored between seven and nine points (55%), 7% received no care during pregnancy, which may be explained by contextual and individual factors. 18,19 A systematic review showed that maternal education, household income, cultural belief and place of residence have an important influence on ANC coverage in LMICs. 20…”
Section: Discussionmentioning
confidence: 99%
“…Latin America and the Caribbean was the region with higher average scores and less variability between countries. Although our results show that globally more than half of women scored between seven and nine points (55%), 7% received no care during pregnancy, which may be explained by contextual and individual factors [ 20 , 21 ]. A systematic review showed that maternal education, household income, cultural belief and place of residence have an important influence on ANC coverage in LMICs [ 22 ].…”
Section: Discussionmentioning
confidence: 65%
“…The Syrian con ict caused destruction to many health facilities in the country (16), consequently interrupting maternal health care for many women and likely deepening divisions in care quality. Postcon ict reconstruction of health services offers a unique opportunity to address the issues that existed precon ict, which contributed to the regional disparities in ANC coverage and patterns of use.…”
Section: Geographic Accessibilitymentioning
confidence: 99%